2018
DOI: 10.1016/j.ejvs.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and Institutionalisation Care Costs after Limb and Visceral Ischaemia Benchmarked Against Stroke: Long-Term Results of a Population Based Cohort Study

Abstract: Objective/backgroundThere are few published data on the acute care or long-term costs after acute/critical limb or visceral ischaemia (ACLVI) events. Using data from patients with acute events in a population based incidence study (Oxford Vascular Study), the present study aimed to determine the long-term costs after an ACLVI event.MethodsAll patients with first ever incident ACLVI from 2002 to 2012 were included. Analysis was based on follow up until January 2017, with all patients having full 5 year follow u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Comparing patients undergoing arthrodesis or amputation for a failed two‐stage, these studies have limited numbers but identified similar functional outcomes and complication rates along with high satisfaction in the amputation group 16,25 . There is no evidence reviewing economic cost of amputation for PJI versus a two‐stage revision, however two‐stage revision TKA carries significant economic costs and there is likely a cost benefit of AKA 5,7,8,26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing patients undergoing arthrodesis or amputation for a failed two‐stage, these studies have limited numbers but identified similar functional outcomes and complication rates along with high satisfaction in the amputation group 16,25 . There is no evidence reviewing economic cost of amputation for PJI versus a two‐stage revision, however two‐stage revision TKA carries significant economic costs and there is likely a cost benefit of AKA 5,7,8,26 …”
Section: Discussionmentioning
confidence: 99%
“…16,25 There is no evidence reviewing economic cost of amputation for PJI versus a two-stage revision, however two-stage revision TKA carries significant economic costs and there is likely a cost benefit of AKA. 5,7,8,26 The authors recommend counselling patients appropriately, discussing all the options and considering less invasive options such as DAIR and suppression or an amputation in patients who have failed a prior two-stage revision TKA. This study did not identify any factors contributing to treatment failure with all repeat twostage revision TKA patients at high risk.…”
Section: Discussionmentioning
confidence: 99%
“…Costs were based on the average of unit cost in the UK NHS, for 2017/18, and were expressed in pounds Sterling (£GBP). The cost estimates for the Markov states and patient cohort were pooled from the national schedule of NHS reference costs [ 33 ] and other published literature [ 11 , 34 , 35 ]. These costs were inflated in accordance to the Hospital and Community Health Services pay and price index (HCHS) [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“… 1 , 5 , 6 The estimated five year economic cost of ALI is over €24 000 per patient. 7 Although venous thromboembolism is a known consequence of malignancy, the relationship between cancer and acute arterial thromboembolism is less well established, 8 with evidence of increased incidence derived primarily from smaller case series. 8 , 9 The increased risk of thromboembolic events in patients with cancer is complex and multifactorial; both the underlying disease and systemic treatments lead to a prothrombotic state, exacerbated by tumorigenic inflammatory responses, abnormal protein metabolism, and haemodynamic compromise leading to subsequent stasis.…”
Section: Introductionmentioning
confidence: 99%